Aqueous Solution Spray Drying Preparations of Binary Amorphous Solid Dispersions - Wenling Zheng; Junni Ke; Kaerdun Liu; Rongrong Xue; Fenghua Chen (Crystals)
Spray drying of poorly water-soluble drugs in organic solvents is a mature process in the preparation of drugs amorphous solids dispersions (ASDs). The use of organic solvents is under increasing environmental protection and safety pressure and restricts the application of advanced polymers as proteins which are usually insoluble and unstable in organic solvents. Aqueous solution spray drying technology is a candidate method for preparing ASDs without the use of organic solvents. Increasing temperature and adding volatile additives can improve the solubility of poorly water-soluble drugs in water without introducing additional components and energy needed. In this work, ammonia assisted aqueous solution spray drying method was successfully used to prepare various ASDs of indomethacin (25%) with synthetic polymers as polyvinylpyrrolidone and proteins as β-lactoglobulin, lactalbumin hydrolysate, bovine serum albumin, with high yields, special micro golfs morphology, precise compositions and longtime stabilities, compared to high-temperature aqueous solution spray drying method. ASDs with lactalbumin hydrolysate and bovine serum albumin show better dissolution profiles than other ASDs. Aqueous solution spray drying is easily extended to prepare the ASDs of sulfamerazine and celecoxib, providing a possibility to avoid the use of organic solvents in advanced ASDs preparations via spray drying.